Layanan konseling kelompok untuk mereduksi stres belajar siswa - Andri Sopian Sopandi; Afiatin Nisa; Sabrina Dachmiati (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
one fact that was difficult to refute is that learning stress is always experienced by students. One effort that is considered capable of reducing learning stress is group counseling. This study aims to determine whether group counseling was able to reduce learning stress in students. This study was conducted with experimental activities. The design used is one group pretest-posttest control group. The sample of this study amounted to nine people who were drawn purposively. Data were collected through a learning stress scale. The research hypotheses were answered using the sign test. The results showed that group counseling services were able to reduce learning stress.